Analysis of Lexical Meaning in Marriage Terms of the Batak Toba Culture - Lisa Sartika Br. Sitompul; Achmad Yudhi (Lakhomi Journal Scientific Journal of Culture, 2022)
This study aims to analyze the terms and describe the lexical meaning contained in the term marriage of the Toba Batak tribe. The author uses a qualitative research method with a descriptive approach and the data collection techniques in this study are: observation, interviews, and listening and note-taking techniques. The results showed that there were eleven terms and their lexical meanings in the marriages of the Batak Toba tribe, namely Mahiturun or Mahuempe, Panoroni, Mangalua, Mangabing Boru, Marimbang or Tungkot, Singkap Rere, Manghabia, Parumaen di Losung, Marsonduk Hela, Manggogoi, Dipaorohon. The results of this analysis indicate that in general, the meaning contained in the term Batak Toba marriage found in Medan City is about messages in the order of social life that contain moral and cultural values in the Toba Batak tribal community.